2022
DOI: 10.1186/s13148-022-01289-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and expression profiles of placenta and umbilical cord blood reveal the characteristics of gestational diabetes mellitus patients and offspring

Abstract: Background Gestational diabetes mellitus (GDM) is a common pregnancy-specific disease and is growing at an alarming rate worldwide, which can negatively affect the health of pregnant women and fetuses. However, most studies are limited to one tissue, placenta or umbilical cord blood, usually with one omics assay. It is thus difficult to systematically reveal the molecular mechanism of GDM and the key influencing factors on pregnant women and offspring. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Pathway analysis found DNAm changes related to T2D and insulin resistance pathways. No data on foetal sex Lu et al, 2022 [ 88 ] 80 GDM 119 Ctrl PS HTR2A Increased pre-pregnancy BMI and GDM was independently associated with lower promoter DNAm in female but not male placentas. Stratified for foetal sex Horvatiček et al, 2022 [ 89 ] 34 GDM 46 Ctrl PS LEP Higher DNAm in placenta from women with GDM of South Asian ethnicity but not European ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Pathway analysis found DNAm changes related to T2D and insulin resistance pathways. No data on foetal sex Lu et al, 2022 [ 88 ] 80 GDM 119 Ctrl PS HTR2A Increased pre-pregnancy BMI and GDM was independently associated with lower promoter DNAm in female but not male placentas. Stratified for foetal sex Horvatiček et al, 2022 [ 89 ] 34 GDM 46 Ctrl PS LEP Higher DNAm in placenta from women with GDM of South Asian ethnicity but not European ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord blood testing monitors the fetus's health during development in the clinical setting [25]. However, detecting DNA methylation in the cord blood of GDM pregnant women is not ideal [17,22]. To improve this situation, this study reduced the in uence of other characteristics on the results at the sample collection level.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the in uence of other characteristics on the results, in this study, we recruited pregnant women at the sample collection level with no signi cant differences in other attributes except OGTT characteristics. If there are other features, covariance correction will be carried out [17], but the data obtained by covariance correction are not actual data. For the correctness of the data, it is suggested that the test samples should be strictly screened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated phosphatidic acid may play a role in mTORC1 signaling, thereby contributing to insulin resistance [ 110 , 112 ], while betaine is important for methylation via the action of betaine-homocysteine S-methyltransferase [ 111 ]. Dysregulated phospholipase D signaling, and hypermethylation that alters genomic regions related to insulin resistance, has been observed in GDM [ 113 ]. Furthermore, elevated betaine-homocysteine S-methyltransferase mRNA has been observed in diabetic rats [ 111 ], suggesting the involvement of betaine in insulin resistance development via alterations in methylation, though further research is necessary to fully understand this connection.…”
Section: Other Metabolic Pathways Alteredmentioning
confidence: 99%